(3GdCMcGe aj Yde GdejbGJs - (3Sgd Hf HTQ Hf MHjH Hf gGfj, CHh YKeGf GdESQGFjdj,J (B235 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3GYde Cf GdHQhL GdGKfG YTQ efgG SJg PchQ hSJg EfGK aGdMed PcQ fgGQi s
(3BNQgG (B:s
(3aEPG cGfJ GdSYhO ai GdHQL ef GdWGdY Ch JfXQ Edjg Ch cGf s
(3GdfSNI ZjQ cGedgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B142 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B283s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B12 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B6 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3Gdadcs